Estudio de factibilidad para la creacion de una microempresa para la producción y comercialización de harina de plátano dominico en el cantón Quevedo, año 2012-2013. - Guaicha Linares, Griselda Jacinta (2014)
This research will be aimed at improving the nutritional level in the canton Quevedo, particularly in the parish of Hope, by making use of bananas produced in the area, through the production and marketing of banana flour. This gives the banana into flour with high nutrition. He had as main objective to carry out a feasibility study for the installation of an industrial plant producing Dominican banana flour that meets all the necessary requirements in terms of economic, environmental and legal technology. To achieve these objectives recollected data at both primary and secondary level. In should be noted that much of the information obtained on the potential unmet demand for this product was collected directly in the parish hopes Canton Quevedo, through surveys of owners of retail stores and the population of families said parish. In the first chapter of the thesis, the introduction mentioned, the current situation is analyzed through the problem statement, objectives and justification are formulated. In the second chapter a thorough study of market research using tools such as surveys are conducted. In the third chapter the technical study is performed by determining the size, location, and project engineering. In the fourth chapter the economic and financial evaluation of the profitability of the project is analyzed to conclude that the project is feasible to perform according to the results of the information.